2008
DOI: 10.1007/s11999-007-0043-0
|View full text |Cite
|
Sign up to set email alerts
|

Retroacetabular Stress-shielding in THA

Abstract: We conducted a randomized clinical trial to compare periacetabular bone density changes after total hip arthroplasty using press-fit components with soft and hard liner materials. Bone density changes were assessed using quantitative computed tomography-assisted osteodensitometry. Twenty press-fit cups with alumina ceramic liners and 20 press-fit cups with highly cross-linked polyethylene liners were included; the nonoperated contralateral side was used as the control. Computed tomography scans were performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 21 publications
(21 reference statements)
3
18
1
Order By: Relevance
“…This is in accordance with the recent report from Yahia et al [13] where similar results were found 2 years postoperative. In contrast to other studies, where a 3% to 35% decrease of cranial acetabular BMD was seen after the placement of a press-fit cup [7,9,23,26,27], we only found a significant decrease for one of the two cranial ROIs in the THA group. As confirmed in other studies we found the most rapid changes in BMD in the first 6 months after surgery, but (smaller) BMD changes still occurred until 24 months [27][28][29].…”
Section: Discussioncontrasting
confidence: 99%
“…This is in accordance with the recent report from Yahia et al [13] where similar results were found 2 years postoperative. In contrast to other studies, where a 3% to 35% decrease of cranial acetabular BMD was seen after the placement of a press-fit cup [7,9,23,26,27], we only found a significant decrease for one of the two cranial ROIs in the THA group. As confirmed in other studies we found the most rapid changes in BMD in the first 6 months after surgery, but (smaller) BMD changes still occurred until 24 months [27][28][29].…”
Section: Discussioncontrasting
confidence: 99%
“…This study's results are corroborated by clinical DEXA scan measurements (Wright et al, 2001;Stolk et al, 2004;Laursen et al, 2007;Pitto et al, 2008;Mueller et al, 2009;Meneghini et al, 2010), cadaveric implant-bone load distribution measurements (Widmer et al, 2002) and previously published numerical predictions (Thompson et al, 2002;Manley et al, 2006) which indicated that stiffer metal cups load the superior acetabular rim cortex preferentially, whereas polymeric cups transferred load more evenly. Implant material is not the only factor; clinical evidence has shown that cemented cups produce a more natural load transfer pattern than press-fitted implants (Mueller et al, 2009).…”
Section: Discussionsupporting
confidence: 80%
“…Clinical radiographic measurements have indicated that contemporary cementless acetabular cups preferentially load the acetabular rim, and shield the central ilium from load (Wright et al, 2001;Pitto et al, 2008). This has been identified by a significant loss of bone mineral density superior to the pole of cementless cups, which stabilises after the first postoperative year (Sabo et al, 1998;Wright et al, 2001;Stolk et al, 2004;Laursen et al, 2007;Pitto et al, 2008;Meneghini et al, 2010) indicating an adaptive process. The results confirm the hypothesis, with a CFR-PEEK cup generating a smaller average increase in cortex strains, and less acetabular rim cortex strain concentration than a CoCr cup.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations